PERJANJIAN BAKU MENURUT PERPEKTIF PENGUSAHA, KONSUMEN DAN KEPASTIAN HUKUM DALAM UNDANG UNDANG PERLINDUNGAN KONSUMEN - Huqmi Adhelia, Olivhien (Universitas Ekasakti, 2023)
Agreements are common things that occur in a form of legal relationship between one individual and another individual or even with a legal entity. As for why the parties want to enter into legal relations is because of the interests between one another and the will of each party. Meanwhile, an engagement is a legal relationship between two people, both individuals and institutions, in which one party has an obligation to fulfill these needs and the other party is obliged to meet these needs. Contract clauses function to accommodate the interests of all parties involved in the agreement. Starting from negotiation or bargaining is an alternative for the parties to carry out the contract and carry out every need stated in the contract clause.